Constructing a Cashless Lifestyle through Word-of-Mouth-Mediated Social Normalization: A Phenomenological Study of QRIS Users at Universitas Negeri Jakarta - Viny Roberkah; Najwa Amanda; Nur Azizah (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
This study examines how word-of-mouth (WOM) communication constructs a cashless lifestyle through the Quick Response Code Indonesian Standard (QRIS) among Universitas Negeri Jakarta students. Unlike previous research that mainly treats WOM as a quantitative predictor of technology adoption, this study views WOM as a lived interpersonal process through which payment meanings, norms, and routines are negotiated. Using Moustakas’s transcendental phenomenology, data were collected through in-depth interviews and non-participant observations with eight active QRIS users aged 18–22 years. Analysis involved epoché, horizonalization, thematic clustering, and synthesis of textural and structural descriptions. The findings reveal a recurring process: peers provide initial social proof, users validate QRIS through shared transaction experiences, and satisfied users become recommenders who reinforce cashless norms. This process normalizes QRIS while students continue negotiating infrastructural constraints and mixed financial consequences. The study introduces the concept of WOM-mediated social normalization, showing that WOM not only predicts adoption but also functions as a norm-producing mechanism that transforms QRIS into an ordinary campus practice. The findings extend interpersonal communication and innovation-diffusion perspectives and support peer-based financial literacy initiatives.